2022
DOI: 10.1108/heswbl-05-2022-0105
|View full text |Cite
|
Sign up to set email alerts
|

Trends in entrepreneurship education: a systematic literature review

Abstract: PurposeThis systematic literature review provides an overview of the entrepreneurship education research, by outlining the recent trends of research on entrepreneurship education. This research study has two primary goals. First one is the identification and categorization of the entrepreneurship education in scientific research by providing sequential distribution of published articles, and the research output of scientific journals, authors, and different countries. Another goal is to recognize the themes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 79 publications
3
2
0
Order By: Relevance
“…The results presented extend previous research addressing above all entrepreneurial intention as the main EE impact indicator (Zhang et al. , 2022; Shabbir et al. , 2022; Kuratko et al.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results presented extend previous research addressing above all entrepreneurial intention as the main EE impact indicator (Zhang et al. , 2022; Shabbir et al. , 2022; Kuratko et al.…”
Section: Discussionsupporting
confidence: 88%
“…This research is focused mainly on the effect of entrepreneurial education on students' entrepreneurial actions. The results presented extend previous research addressing above all entrepreneurial intention as the main EE impact indicator (Zhang et al, 2022;Shabbir et al, 2022;Kuratko et al, 2021;Nabi et al, 2017;Bae et al, 2014). In line with Chen et al's (2018) proposal, students' entrepreneurial actions have been conceptualized through the abstract-concrete continuum, which is an original conceptualization matching the effectuation and bricolage logics.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This study provided an insightful assessment of 1017 research articles on entrepreneurship education published between 2014 and November 2023 using bibliometric analysis methods, revealing the field's multidisciplinary characteristics and development trends. This study found that the disciplinary areas involved in entrepreneurship education were consistent with the results of Shabbir et al (2022), indicating that entrepreneurship education has a significant impact not only in the fields of business and management but also in other disciplines, such as social sciences, especially in recent years, where it has been more inclined towards social science fields. This study found that the number of research papers on entrepreneurship education has increased significantly in the past decade, which is consistent with the research of Sreenivasan and Suresh (2023), reflecting the continued attention of academics in this field.…”
Section: Discussionsupporting
confidence: 83%
“…Although Sreenivasan and Suresh (2023) have mapped the growth trend of nearly 20 years from the perspective of entrepreneurship education research, they have not conducted in-depth research on specific citations, such as articles and authors, countries, journal sources, and many potential fields are still waiting to be studied. On the other hand, some researchers have used systematic analysis to review entrepreneurship education (Banha et al, 2022;Shabbir et al, 2022). Although these in-depth studies examined entrepreneurship education from different perspectives, revealing its current status, future development direction, research hotspots and key influences, there are also some limitations.…”
Section: Introductionmentioning
confidence: 99%